VARIETIES AND EARLY CULTURE OF CELERY IN UZBEKISTAN (CAHIERS MAGELLANES-NS, 2024)
Abstract. The article presents the results of research on the cultivation of celery in the conditions of the Samarkand region. When growing different varieties of celery, the highest plant height was observed in the Kartuli and Samurai varieties. According to the dynamics of biometric indicators - the largest number of leaves, the size of the assimilation surface of leaves and the number of shoots, the varieties Kartuli (respectively, 84.7 pcs., 1330.6 cm2 and 5.9 pcs.) and Samurai (respectively, 83.9 pcs., 1318.4 cm2 and 5.8 pcs.). The highest indicators for the average weight of one plant (178.3 g), yield (28.7t/ha), profits (50.3 million soums) per hectare and profitability levels (197.7%) were obtained when growing Kartuli variety plants. The resulting yield for the Kartuli variety was 142.7% higher than that of the standard Serbarg variety (20.1 t/ha).